Correction: Substituted bidentate and ancillary ligands modulate the bioimaging properties of the classical Re(i) tricarbonyl core with yeasts and bacteria. (8th March 2017) - Carreño, Alexander; Aros, Alejandra E.; Otero, Carolina; Polanco, Rubén; Gacitúa, Manuel; Arratia-Pérez, Ramiro; Fuentes, Juan A.
Abstract : Correction for 'Substituted bidentate and ancillary ligands modulate the bioimaging properties of the classical Re(i ) tricarbonyl core with yeasts and bacteria' by Alexander Carreño et al., New J. Chem., 2017, 41, 2140–2147.